Economic Return Quantity Model for a Multi-type Empty Container Management with Possible Storage Constraint and Shared Cost of Shipping. Issue 4 (1st October 2020) - Adetunji, Olufemi; Yadavalli, Sarma; AlRikabi, Rafid; Makoena, Sebatjane
Abstract: Containerization has been said to be one of the most significant innovations of port management in the last century. Some ports usually tend to be more export driven while some others are import driven. This imbalance in the number of inbound and outbound containers necessitates movement of containers from locations or surplus to those of deficit. A port needs to cater for not only the level of containers required, but also the variety. Many factors affect the cost efficiency of container movement, and hence, that of port operations, and these need to be managed in an integrated manner to optimize cost in a port. We studied the management of a multi-type container system in a port where there can be savings from joint movement of containers, both for empty return and for procurement of replacement containers, and where there is limited storage capacity. We developed a model to determine the optimal integrated return and purchase cycle times and quantities. We illustrated the solution approach with a numerical example and performed sensitivity analysis. We believe this problem is rife and the model can guide the management of container return and replenishment in ports operations.